The Divine Pedagogy as a Model for Online Education - Gresham, John (2006)
In addition to the pragmatic concerns that often drive the use of technology in theological education, there is a need to develop theological justification and direction for online education. Several Roman Catholic Church documents propose the “divine pedagogy,” the manner in which God teaches the human race, as a model for catechesis or religious education. This can provide a rich resource for developing a theological pedagogy for online education. This is especially relevant to the justification for online education, because critics sometimes refer to the incarnational character of the divine pedagogy to argue against the disembodied nature of virtual education. This article addresses such criticisms and more constructively, relates several aspects of the divine pedagogy such as adaptation, community, and participation to teaching and learning in the online environment. (This paper was presented at Theology and Pedagogy in Cyberspace II conference in Evanston, Ill. on April 17, 2004.)
Keywords: Student; Embodied; learn; teach; Pedagogy